Effectiveness of Implementing Project Based Learning in Improving Students' Problem Solving Abilities - Adila Solida; Andy Amir (Badan Penerbit STIEPARI Press, 2023)
The ability to analyze problems is one of the learning outcomes that students must master. The majority of student learning outcomes still fall into the category of requiring a project-based learning innovation that can provide maximum opportunities for students to be directly involved in creating real and active projects in the learning process through the application of case method project-based learning. The aim of this research is to analyze the effectiveness of implementing project-based learning on problem-solving abilities in health ethics and law courses. The research was conducted at the Public Health Science Study Program at Jambi University on first semester students. The research design was a quasi-experiment involving 200 students. The instruments used are assessment sheets and observation sheets. Data collection was carried out before and after implementing the learning. Data processing and analysis used the T test. The research results showed that there was significant effectiveness in implementing project-based learning in increasing students' problem-solving abilities. The application of project-based learning contributes to honing problem-solving skills so that it is recommended that project-based learning methods be used in every course in higher education.